Articular damages in multi-generational female offspring due to prenatal caffeine exposure correlates with H3K9 deacetylation of TGFβ signaling pathway. (September 2020) - Zhao, Zhe; Qin, Jun; Pei, Linguo; He, Zheng; Luo, Hanwen; Magdalou, Jacques; Chen, Liaobin; Wang, Hui
Abstract: Adverse environment during pregnancy could lead to maternal glucocorticoid overexposure in utero, and then induce the intrauterine growth retardation (IUGR) and the programmed change in cartilage development. The transforming growth factor β (TGFβ) signaling pathway plays a crucial role in the process of chondrogenesis, cartilage growth, development, maturation, and phenotype maintenance. Our previous results had shown that prenatal caffeine exposure (PCE) could result in the damaged articular cartilage in offspring rats. However, whether this change could transmit to multiple generations was still unknown. In this study, pregnant Wistar rats received either saline or caffeine (120 mg/kg, i.g.) once daily from gestational day 9–20 (GD9−20). The female offspring mated with normal male rats to generate the following generations. We obtained the articular cartilages in subsequent F1 to F3 female offspring. The H3K9 acetylation and expression of the TGFβ signaling pathway were detected; the content of the cartilage matrix was detected. The results showed that PCE reduced the H3K9 acetylation and the expression of the TGFβ signaling pathway, then reduced the extracellular matrix in F1, F2, and F3 generations. in vitro, corticosterone could induce the H3K9 deacetylation of the TGFβ signaling pathway, thus inhibiting the expression of the TGFβ signaling pathway and extracellular matrix. The overall results revealed that PCE induced a multi-generational damaged articular cartilage in female offspring rats, which was partially related to the maternal high glucocorticoid-induced H3K9 hypoacetylation of TGFβ signaling pathway.